ELDERLY PEOPLE WITH DIFFERENT TYPES OF NUTRITIONAL BEHAVIOR HEALTH STATUS AND QUALITY OF LIFE - Chobanov, R.A.; Hajiyeva, Y.H.; Bakhishli, F.G. (World of Medicine and Biology, 2025)
The purpose of the study was to assess the distribution of nutritional behavior types in different age groups of elderly people and their health status and quality of life. The research was conducted on the basis of 4 city polyclinics (patients, guests), 4 schools (parents) and 14 different companies and departments (employees) of Baku city. The types and social and hygienic aspects of the formation of feeding behavior were determined by a blind survey using the international DEBQ questionnaire. Quality of life was determined by the SF–36 international questionnaire. In total, the health of elderly people can be assessed as unsatisfactory according to the survey. Almost all types of nutritional behavior did not exceed 0.52 points, which corresponds to a low assessment of self-health. Health and quality of life indicators were lower for all types of nutritional behavior, only in mixed nutritional behavior type their indicators were more positive.